2000
DOI: 10.1179/bct.2000.99.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environment on delayed failure of alumina ceramics

Abstract: dissociating. This mechanism is predominant for highly ionic solids, e.g. for magnesium halides. Dynamic fatigue testing of various alumina ceramics inIn alumina ceramics processing, sintering additives are humid air, water, acidic, and alkaline environments was used which form specific grain boundary phases that can performed. It is shown that the fatigue resistance of influence or control the subcritical crack growth process. glass bonded alumina in air and in water is significantlyThe main component of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
1
16
0
3
Order By: Relevance
“…Actually, a small quantity of glass could seriously deteriorate the subcritical crack growth resistance of alumina ceramics. For example, Barinov et al 28 reported an n value of 60.1 for a high-purity alumina (99.5 wt.% alumina, 0.4 wt.% MgO, and 0.1% silica and alkali oxides). When 5 wt.% glasses were added to the alumina as sintering aids, the n values decrease to 32.3-35.9.…”
Section: Discussionmentioning
confidence: 97%
“…Actually, a small quantity of glass could seriously deteriorate the subcritical crack growth resistance of alumina ceramics. For example, Barinov et al 28 reported an n value of 60.1 for a high-purity alumina (99.5 wt.% alumina, 0.4 wt.% MgO, and 0.1% silica and alkali oxides). When 5 wt.% glasses were added to the alumina as sintering aids, the n values decrease to 32.3-35.9.…”
Section: Discussionmentioning
confidence: 97%
“…The glass phase is more susceptible to stress-corrosion, and SCG occurs through the bulk glass phase or the glass-ceramic interface [18, 21, 26]. Previous studies also observed significant influence of the glass matrix in the slow crack growth behavior of these glass-infiltrated composites [26, 42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42] However, these tend toward more continuous controlled processes, whereas spallation tends toward instantaneous step events, as shown by the AE experiments of Reference 8. Here it had been argued that moisture provided a trigger for the loaded gun of a sulfurexpanded and weakened interface.…”
Section: Proposed Modelmentioning
confidence: 99%